2015
DOI: 10.11114/jets.v4i2.1145
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Number Sense Performance of Secondary School Students in Turkey

Abstract: The purpose of this study is to investigate the number sense performance of secondary school students according to grade level, gender and the components of number sense. A descriptive survey design was used to collect data. A total of 576 secondary school students (291 girls and 285 boys) participated in the study. The results revealed that the number sense performance of secondary school students was very low for each grade level. Among the components of number sense, the lowest mean score was observed in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
(40 reference statements)
1
12
2
3
Order By: Relevance
“…It was detected that there is a significant difference on the achievement of NST, CTF and UB dimensions and no significant difference on the achievement of FC dimension. In terms of NST, this finding was parallel to result of [20] and contradicted result of [12]. Because, [12] stated that the success of the number sense decreased when class level increased.…”
Section: Resultscontrasting
confidence: 53%
“…It was detected that there is a significant difference on the achievement of NST, CTF and UB dimensions and no significant difference on the achievement of FC dimension. In terms of NST, this finding was parallel to result of [20] and contradicted result of [12]. Because, [12] stated that the success of the number sense decreased when class level increased.…”
Section: Resultscontrasting
confidence: 53%
“…Similarly, Chattopadhyay, Sarkar, and Koner (2017) also reported male students outperforming their female counterparts in making sense of numbers through a paper and pencil test. Akkaya (2016) in another study reported that although no significant differences between genders were found, the performance of male students was higher than female students across grades.…”
Section: Discussion Of Findingsmentioning
confidence: 85%
“…Mohamed and Johnny (2010) also highlighted that many previous studies, both local and international, have revealed that students have poor understanding in making sense of numbers. For example, Akkaya (2016) reported that the number sense achievement of secondary school students in Turkey was also very low for each grade level. These findings reveal that students' low level sense of numbers is also prevalent in other countries.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Even so, if having a number sense ability, then students (especially preservice mathematics teachers) can solve the mathematical problems related to it better. Many studies have shown that various pre-service teacher backgrounds have low results in understanding numbers when given tests related to the component of number sense (Akkaya, 2015;Sengul, 2013;Yang, Reys, & Reys, 2009;Yaman, 2015;Aktas & Ozdemir, 2017). Besides, the results of research conducted by Sengul (2013) show that pre-service elementary teachers' number sense is still deficient and tends to use a "rule-based method" rather than "number sense" on each component tested (Koleza & Koleli, 2014).…”
mentioning
confidence: 99%